ANALISI PENGARUH KONTIBUSI DAN EFEKTIVITAS PAJAK HOTEL DAN RESTORAN TERHADAP PAD PADA BADAN PEMERIKSAAN KEUANGAN (BPK) KOTA JAMBI TAHUN 2022-2024 - Suci Rahma Dani; Vera Amalia; Eka Julianti Efris Saputri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the contribution of Hotel Tax and Restaurant Tax to Local Own-Source Revenue (PAD) as well as the effectiveness of their collection in the City of Jambi from 2022 to 2024. The research method used is a quantitative method with a descriptive approach. The data used consisted of target and actual figures for Hotel Tax, Restaurant Tax, and the City of Jambi’s PAD, obtained from the Jambi Provincial Office of the Supreme Audit Agency (BPK). Data analysis was conducted using contribution analysis and effectiveness analysis. The results of the study indicate that the contribution of Hotel Tax to the City of Jambi’s PAD is very low, amounting to 4.90% in 2022, 5.40% in 2023, and 5.40% in 2024. Meanwhile, the contribution from the Restaurant Tax was greater than that from the Hotel Tax, amounting to 14.32% in 2022, 15.94% in 2023, and 17.06% in 2024. In terms of effectiveness, the Hotel Tax had effectiveness rates of 83.90%, 80.76%, and 86.95%, which fall into the “fairly effective” category. Meanwhile, the effectiveness of the Restaurant Tax was 78.25% in 2022 (less effective), increasing to 84.08% in 2023 and 88.69% in 2024 (fairly effective). The research results indicate that the effectiveness of Hotel Tax and Restaurant Tax collection has a positive impact on the increase in Jambi City’s local revenue (PAD). The higher the effectiveness of tax collection, the greater its contribution to supporting local revenue.